Utility of DECAF Score as A Bed Side Tool in Predicting Outcomes in Patient with Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Pandey, Parishrut Prasad; Vaidhya, Shreeju; Karki, Ashyashree; Dahal, Bibesh; Jaiswal, Vedhant; Bishwokarma, Bikash (Journal of College of Medical Sciences-Nepal, 2024)
Background Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) can be fatal. It is the third leading cause of death worldwide, causing 3.23 million deaths in 2019. The DECAF (Dyspnea, Eosinopenia, Consolidation, Acidemia, Atrial Fibrillation) score is a widely used system for predicting the survival of patients with AECOPD. It uses Routinely available indices, is quick and can be easily used by clinicians to identify sick patients who need vigilant care. Methods A cross sectional study was conducted at College of Medical Sciences Teaching Hospital, Bharatpur for 6 months. Patients with COPD meeting inclusion Criteria were selected and the DECAF score at time of admission was calculated. Their duration of hospital stay, use of ventilator and final outcome were noted and its relation to the Decaf score was analysed. Results A total of 163 patients (Male-87, Female-76) were included in the study. The mean age of the patients was 70 ±10 years and mean duration of hospital stay was 5.91±2.19 days. There is significant relationship between DECAF score and the mortality (p-value < 0.001) with higher the score higher the chance of not improving. Analysis between the DECAF score and length of Hospital stay by regression equation found the regression coefficient 0.410 to be significant (p-value < 0.001) indicating that if DECAF score increases by one, the length of hospital stay will also increases by 0.41 day. Conclusions Patients with a DECAF score of four or higher have a significant risk of mortality as well as long duration of hospital stay. Thus, DECAF is a simple tool that incorporates routinely available indices to predict adverse outcomes in AECOPD.